Key bottlenecks to the provision of safe obstetric anaesthesia in low- income countries; a cross-sectional survey of 64 hospitals in Uganda - Isabella Epiu; Agnes Wabule; Andrew Kambugu; Harriet Mayanja-Kizza; Jossy Verel Bahe Tindimwebwa; Gerald Dubowitz (BMC, 2017)
Abstract Background Despite recent advances in surgery and anaesthesia which significantly improve safety, many health facilities in low-and middle-income countries (LMICs) remain chronically under-resourced with inability to cope effectively with serious obstetric complications (Knight et al., PLoS One 8:e63846, 2013). As a result many of these countries still have unacceptably high maternal and neonatal mortality rates. Recent data at the national referral hospitals in East Africa reported that none of the national referral hospitals met the World Federation of Societies of Anesthesiologists (WFSA) international standards required to provide safe obstetric anaesthesia (Epiu I: Challenges of Anesthesia in Low-and Middle-Income Countries. WFSA; 2014 http://wfsa.newsweaver.com/Newsletter/p8c8ta4ri7a1wsacct9y3u?a=2&p=47730565&t=27996496 ). In spite of this evidence, factors contributing to maternal mortality related to anaesthesia in LMICs and the magnitude of these issues have not been comprehensively studied. We therefore set out to assess regional referral, district, private for profit and private not-for profit hospitals in Uganda. Methods We conducted a cross-sectional survey at 64 government and private hospitals in Uganda using pre-set questionnaires to the anaesthetists and hospital directors. Access to the minimum requirements for safe obstetric anaesthesia according to WFSA guidelines were also checked using a checklist for operating and recovery rooms. Results Response rate was 100% following personal interviews of anaesthetists, and hospital directors. Only 3 of the 64 (5%) of the hospitals had all requirements available to meet the WFSA International guidelines for safe anaesthesia. Additionally, 54/64 (84%) did not have a trained physician anaesthetist and 5/64 (8%) had no trained providers for anaesthesia at all. Frequent shortages of drugs were reported for regional/neuroaxial anaesthesia, and other essential drugs were often lacking such as antacids and antihypertensives. We noted that many of the anaesthesia machines present were obsolete models without functional safety alarms and/or mechanical ventilators. Continuous ECG was only available in 3/64 (5%) of hospitals. Conclusion We conclude that there is a significant lack of essential equipment for the delivery of safe anaesthesia across this region. This is compounded by the shortage of trained providers and inadequate supervision. It is therefore essential to strengthen anaesthesia services by addressing these specific deficiencies. This will include improved training of associate clinicians, training more physician anaesthetists and providing the basic equipment required to provide safe and effective care. These services are key components of comprehensive emergency obstetric care and anaesthetists are crucial in managing critically ill mothers and ensuring good surgical outcomes.